If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + 5 = 5p + -31 Reorder the terms: 5 + 9p = 5p + -31 Reorder the terms: 5 + 9p = -31 + 5p Solving 5 + 9p = -31 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 5 + 9p + -5p = -31 + 5p + -5p Combine like terms: 9p + -5p = 4p 5 + 4p = -31 + 5p + -5p Combine like terms: 5p + -5p = 0 5 + 4p = -31 + 0 5 + 4p = -31 Add '-5' to each side of the equation. 5 + -5 + 4p = -31 + -5 Combine like terms: 5 + -5 = 0 0 + 4p = -31 + -5 4p = -31 + -5 Combine like terms: -31 + -5 = -36 4p = -36 Divide each side by '4'. p = -9 Simplifying p = -9
| 7.1=9.5-0.3x | | Yx=z+2 | | 4-t/2=1 | | 3x-33=2x+16 | | 11x+2-4x=17 | | 2x-20=80-60 | | 17+-3c=4c+3 | | 14a^2+6a-5a^3-2a^2-5a^2-4a^4= | | s/3+5=8 | | 3x+1+3x+2=12 | | 27-3c=4c+3 | | 5(18)= | | 4x-30+3x+12=180 | | 28.18=5g+3.88 | | 5.3(8-(7-(3x+4))+6)=-18.7 | | -4+7x=0 | | 12x-x-71=83 | | 42=4x+2[-x+15] | | 0.8(x+9)=0.5x+6.3 | | 11x+6-4x=17 | | -1x+4x-38=-10x+11 | | =37.92+0.50x | | 24=-6(2x) | | -8w^3+50w=0 | | 9z+7z+2z-8= | | 8z+6=7z+5 | | 7y+6x=-2 | | 9(x-5)=22 | | 2a^2-2ab+b= | | -n/3=6 | | (5y^2+7y-7)-(4y^2-6y+1)+(8y^2-6y+3)= | | (h-8)=(h+10) |